2007
DOI: 10.1167/iovs.06-1131
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity to Light-Induced Damage in a Mouse Model of Autosomal Dominant Retinal Disease

Abstract: Expression of a human hT17M mutant rhodopsin transgene in mice is associated with photoreceptor apoptosis in response to moderate exposure to light. This phenotype was not observed in nontransgenic littermates or in mice expressing an hP23H mutant human rhodopsin transgene. The results suggest that elimination of the glycosylation site at N15 is associated with increased sensitivity to light-induced damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…Thus, the observation of an increased level of cleaved caspase-7 (up to fourfold) in P23H-3 RHO retina is not surprising. Photoreceptors are known to die by apoptosis in this model (28). Our studies have therefore demonstrated the importance of the UPR in clinically relevant model of a human disease.…”
Section: Discussionsupporting
confidence: 53%
“…Thus, the observation of an increased level of cleaved caspase-7 (up to fourfold) in P23H-3 RHO retina is not surprising. Photoreceptors are known to die by apoptosis in this model (28). Our studies have therefore demonstrated the importance of the UPR in clinically relevant model of a human disease.…”
Section: Discussionsupporting
confidence: 53%
“…These results imply that in vivo, a misfolded monomer of P23H opsin can also induce co-aggregation with WT rhodopsin preventing rod outer segment (ROS) formation. This dominant negative effect on ROS formation has been considered as the underlying reason for the adRP inheritance of P23H in humans.The retinal structure in heterozygous transgenic mice and rats expressing the P23H opsin partially mimics that of adRP in humans carrying this mutation (15)(16)(17)(18)(19). Mislocalization of the P23H opsin in the retina also has been reported in transgenic animal models (20), and this causes an abnormally reduced response to light (21).…”
mentioning
confidence: 88%
“…The retinal structure in heterozygous transgenic mice and rats expressing the P23H opsin partially mimics that of adRP in humans carrying this mutation (15)(16)(17)(18)(19). Mislocalization of the P23H opsin in the retina also has been reported in transgenic animal models (20), and this causes an abnormally reduced response to light (21).…”
mentioning
confidence: 88%
“…Mutations of these residues or their surrounding glycosylation consensus sequences (T4K, N15S, and T17M) are linked to a subset of RP known as sector RP in which the inferior retina is primarily affected, potentially attributable to greater light exposure to this region (Fishman et al, 1992;Sullivan et al, 1993;Li et al, 1994;van den Born et al, 1994). Furthermore, both transgenic mice expressing human T17M rhodopsin (White et al, 2007) and a naturally occurring dog model harboring a rhodopsin T4R mutation exhibit lightsensitive retinal degeneration (Kijas et al, 2002;Cideciyan et al, 2005). Together, the human disease and animal models suggest that glycosylation plays a crucial role in the structure and/or function of rhodopsin.…”
Section: Introductionmentioning
confidence: 99%